2019
DOI: 10.1002/asia.201900843
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the Filler/Polymer Interface in Metal–Organic Framework‐Based Mixed‐Matrix Membranes to Enhance Gas Separation

Abstract: Traditional films cannotf ully adapt to industrial applicationsa nd to intensified processes. Advanced mixedmatrix membranes comprising metal-organic frameworks (MOF) embedded in ap olymer matrix have been developed with the goal of breaking the trade-offe ffect of traditional polymer membranes and achieving separation performance beyond Robeson's upper limit. The key challenges in the fabrication of MOF-based mixed-matrix membranes are an enhancementi nc ompatibility between the inorganic filler and the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 128 publications
(44 reference statements)
0
39
0
Order By: Relevance
“…In order to achieve industrial adoption, it is essential to understand and develop the performance of the NO-releasing MOF powders when formulated into polymers. There are many studies in the literature regarding MOF-polymer composites (referred to as mixed matrix membranes or MMMs) for applications such as gas separation 44 and water purification. 45 This growing body of work confirms the excellent compatibility of MOFs with a wide variety of polymers, and highlights the ease with which MOFs can be formulated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve industrial adoption, it is essential to understand and develop the performance of the NO-releasing MOF powders when formulated into polymers. There are many studies in the literature regarding MOF-polymer composites (referred to as mixed matrix membranes or MMMs) for applications such as gas separation 44 and water purification. 45 This growing body of work confirms the excellent compatibility of MOFs with a wide variety of polymers, and highlights the ease with which MOFs can be formulated.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, it was found that some rubbery polymers that contain ester groups can bind with the metal nodes within MOFs in chelating interactions. 50 Xiang et al 51 used ZIF-7-NH 2 , an amino-functionalized ZIF-7, as a filler in a crosslinked polyethylene oxide (PEO) matrix for CO 2 /CH 4 separation. They found that there was strong bonding between the metal (zinc) nodes in the filler and the ester groups of the polymer due to the chelating effects.…”
Section: Optimization Of the Polymer-filler Interfacementioning
confidence: 99%
“…Additionally, this combination allowed for the overcoming of the low permeability nature of PBI. In more recent years, it was found that some rubbery polymers that contain ester groups can bind with the metal nodes within MOFs in chelating interactions 50 . Xiang et al 51 used ZIF‐7‐NH 2 , an amino‐functionalized ZIF‐7, as a filler in a cross‐linked polyethylene oxide (PEO) matrix for CO 2 /CH 4 separation.…”
Section: Challenges and Research Trends For Mmmsmentioning
confidence: 99%
“…In the MMMs containing modified SNPs compared to the MMMs containing unmodified SNPs, the permeability of CH 4 and CO 2 gases were higher and that of N 2 was lower. The COOH functional groups of the modified SNPs can effectively enhance the surface affinity toward condensable gases like CO 2 and CH 4 [7,46] and, as a result, the permeability of CH 4 and CO 2 gases and subsequently that of CH 4 /N 2 increases.…”
Section: Effect Of Snps Loadingmentioning
confidence: 99%
“…The success of MMMs is highly dependent on the choice of the polymer matrix and inorganic filler and the control of the interface properties between the polymer chains and filler particles [26,27]. The morphology of MMMs plays a critical role in ensuring preferential gas transport through the inorganic phase rather than the organic phase [5].…”
Section: Introductionmentioning
confidence: 99%